Identification and function analysis of the host cell protein that interacted with Orf virus Bcl-2-like protein ORFV125. (October 2016) - Tian, Hong; Chen, Yan; Wu, Jinyan; Lin, Tong; Liu, Xiangtao
Abstract: Orf virus (ORFV) causes contagious ecthyma, a non-systemic skin disease in sheep and goat. Bioinformatics analysis showed that ORFV125 has Bcl-2-like homologous domain and 3D structurally, it is generally known that Bcl-2 protein is known to be a key protein to control cell apoptosis. Maybe ORFV125 act as a Bcl-2-like manner to control cell apoptosis, but its exact function isn't very clear. So in this study, we use yeast two-hybrid system to identity the putative host cell protein interacting partners of ORFV125, and meanwhile using the data obtained from the Gene Ontology, Uniprot, and Kyoto Encyclopedia of Genes and Genomes databases to analysis the functions and pathways associated with them. Finally, five host proteins were shown to be interacted with ORFV125, including cytochrome b (cytb) gene, GUCY2C, BIRC5, GTF3C6 and SERBP1, we also found that BIRC5 has complex biological functions, can inhibit apoptosis, promote cell transformation and are involved in mitosis, and the interaction network of BIRC5 and ORFV125 were constructed. These findings provide a foundation to better understand the biology of the interactions between ORFV125 and the host proteins with which it directly interacts with and resultant downstream events. Highlights: Our works is the first time to construct the Y2H STCs cDNA library. Cytb gene, GUCY2C, BIRC5, GTF3C6 and SERBP1 were shown to be interacted with ORFV125. Constructed the interaction network of BIRC5 and ORFV125.